Zinc recovery from bioleachate using a microbial electrolysis cell and comparison with selective precipitation - Spiess, Sabine; Kucera, Jiri; Vaculovic, Tomas; Birklbauer, Ludwig; Habermaier, Clemens; Conde, Amaia Sasiain; Mandl, Martin; Haberbauer, Marianne (Frontiers in Microbiology, 2023)
Metal recycling is essential for strengthening a circular economy. Microbial leaching (bioleaching) is an economical and environmentally friendly technology widely used to extract metals from insoluble ores or secondary resources such as dust, ashes, and slags. On the other hand, microbial electrolysis cells (MECs) would offer an energy-efficient application for recovering valuable metals from an aqueous solution. In this study, we investigated a MEC for Zn recovery from metal-laden bioleachate for the first time by applying a constant potential of -100 mV vs. Ag/AgCl (3 M NaCl) on a synthetic wastewater-treating bioanode. Zn was deposited onto the cathode surface with a recovery efficiency of 41±13% and an energy consumption of 2.55 kWh kg-1. For comparison, Zn recovery from zinc sulfate solution resulted in a Zn recovery efficiency of 100±0% and an energy consumption of 0.70 kWh kg-1. Furthermore, selective metal precipitation of the bioleachate was performed. Individual metals were almost completely precipitated from the bioleachate at pH 5 (Al), pH 7 (Zn and Fe), and pH 9 (Mg and Mn).